Evaluación del efecto de varias dosis de purín de lombriz y de cortes en el desarrollo del pasto Brachiaria brizhanta (Marandú) en el cantón Cumandá, provincia de Chimborazo. - Jurado Lara, Fausto Alexander (2019)
The production of pastures in Ecuador is of great importance in the livestock, because it is the main source of food for different species of livestock, especially cattle. The marandú (Brachiaria brizhanta) is native to the African continent. The grass adapts to tropical environmental conditions for its agronomic development. However, the incorrect use and management of pasture production has generated a shortage of food for livestock species. One of the main agronomic activities carried out in pastures, is the fertilization of them, to obtain a production on greater quantity and better quality. This fertilization is carried out by farmers in a conventional manner, directly affecting the environment and the people in charge of carrying out said agricultural work. The use of earthworm humus slurry to be a fertilizer of organic origin prevents damage to the environment and people who are around agricultural production. This work done in order to improve the production of pastures, it was executed by applying several doses of earthworm, acting as an optimizer in the growth of the grass. Corresponding statistical analyzes were performed in a DBCA, through the Duncan test, with the help of the Infostat program. Where it could be determined that the highest dose of 1 000 ml applied slurry earthworm humus in the grass, are the best development was obtained.